Aquatic environment – effective tool for health prevention and hardening (Research Announcements "Heritage BG", 2025)
According to the UN Annual Report on the Happiness Index by Nations, water practices show growth that is higher than the overall growth of all physical leisure activities. Methods: We apply a comparative analysis of applied innovative aqua programs by gender, for people in active age. Results: The immune system health is increased through the hardening effect of the aquatic environment and zone-oriented motor activity, according to gender and age. Aqua programs, backed by scientific evidence of effectiveness, combined with personalised diets, are increasingly desirable and fill the schedule of coaches with 2-3 weeks ahead. Discussion: Aqua practices are an effective tool for health prevention and a successful strategy against panic attacks. Conclusion: Aqua practices are a profitable tool for investing in individual, family and corporate health by raising the level of Well-being. References:Chalakov, Milen. Turnirite po fekhtovka na vsichki orŭzhiya, provedeni v Narodna Republika Bŭlgariya mezhdu 1976-1978 g. Sofiya, 2016, pp. 230-233.Chipeva, Maya. Avangard Prima: Kango dzhemps Aerobika. Sofia, 2019.Dimitrova, Bistra, et al. Smart kognitiven instrumentarium. Vŭnshna otsenka na profesionalni kompetentsii za kadri v Nishov turizŭm. Sofia, 2021, pp. 97-102.Tomova, Tatiana. Menstrualni raztroĭ stva – razpostranenie i proyava. International Scientific journal Smart Innovations in Recreational, Wellness Industry and Niche Tourism, vol. 3, no. 2, 2021, pp. 33-38.Vasileva, Kapka, and Maya Chipeva. Izsledvane i otsenka na dvigatelnata deesposobnost i tekhnicheskite umeniya na studentite v uchebnite chasove po basketbol na tekhnicheskiya universitet Sofiya. International Scientific Journal: Smart Innovations in Recreational, Wellness Industry and Niche Tourism, vol. 2, no. 2, 2019, pp. 22-27.Veselinov, Dimitar. Dialogat v obrazovanieto. Deseti mezhdunaroden esenen nauchno-obrazovatelen forum, Dialogat v obrazovanieto – suvremennost i perspektivi. Sofiya, 2021, pp. 11-16.Chalakov, Milen. "Optimizing the Control of Technical Performance of Forehand Stroke among 12-year Old tennis Players Using Martin’s Sigma Method." Trakia Journal of Sciences, vol. 18, no. 1, 2020, pp. 682-688.Dimitrova, Bistra. "Recreative Industry, Innovations and the Bulgarian Educational Model for Specialised Staff." Proceedings of the International Scientific Congress ‘Applied sports sciences’, Sofia, 2017, pp. 406-410.Dimitrova, Bistra. "Quality Assessment about Standards for Wellness Services and Certified Skills of Specialized Staff." Trakia Journal of Sciences, vol. 17, no. 2, 2019, pp. 143-149.Dimitrova, Bistra. New Smart Educational Model ‘Wellness instructor’. Avangard Prima, Sofia, 2019.Dimitrova, Bistra. "Relationships Between Education and Innovations in the Recreational Industry in Bulgaria." Trakia Journal of Sciences, vol. 18, no. 2, 2020, pp. 143-149.Donev, Jordan, et al. "Comparative Study of Measuring Physical Activity Among Sport Students." International scientific congress ‘Applied sports sciences. Balkan scientific congress of physical education, sports and health’, Sofia, 2019, pp. 369-374.Global Wellness Institute. Economic Report. Miami, 2014, pp. 27-28.Ignatova, Darinka, and Alexandar Iliev. "Motor Qualities and Their Influence on Children’s Development." International Scientific Journal: Smart Innovations in Recreation, Wellness Industry and Niche Tourism, vol. 2, no. 1-2, 2020, pp. 16-44.Ivanova, Vessela. "Influence of Gymnastic Exercises in the Water Environment." International Scientific Journal: Smart Innovations in Recreational, Wellness Industry and Niche Tourism, vol. 1, no. 1, 2019, pp. 53-56.Konchev, Mihail. "Big Data, Neural Network and Predictive Analytics: Application in the Field of Sport." International scientific congress ‘Applied Sports Sciences’ and Balkan scientific congress ‘Physical Education, Sports, Health’, Sofia, 2019, pp. 393-397.Polimenov, Mincho. "Transfer of Innovation in the Service Technology for Increasing the Restaurant Quality Product." International Scientific journal Smart Innovations in Recreational, Wellness Industry and Niche Tourism, vol. 1, no. 2, 2019, pp. 29-35.Trendafilov, Dimitar, and Bistra Dimitrova. "Aqua Spinning as Antistress Health Prevention." Sport Mont, vol. 11, no. 37-39, 2013, pp. 467-473.
Keywords: Water influences; health from nature; health prevention; wellness lifestyle